CBroadcast: an Application Layer Multicast mechanism based on combination of central control and self-organisation. (18th June 2007) - Cui, Yong; Xu, Ke; Wu, Jian-Ping; Song, Lin-Jian
Nowadays Application Layer Multicast (ALM) is widely used in the media transmission through the network, while ALM itself still has some problem on its performance. In this paper, we advance an ALM mechanism based on combination of central-control and self-organisation: CBroadcast which is stable and suitable for the real-time multimedia. In the higher levels special servers with high performance are deployed responsible for the construction and maintenance of mesh network and multicast tree, while in the lower levels a distributed protocol for self-organisation and Mesh-first strategy is adopted. In addition, multicast technologies both in application layer and network layer are combined to achieve higher performance. In the end of the paper, an experiment is delicately designed to show the advantage of CBroadcast.